Metastasis of Malignant Melanoma to Urinary Bladder: A Case Report and Review of the Literature - Rashna Meunier; Gyan Pareek; Ali Amin (Hindawi Limited, 2015)
Aims. Metastatic malignant melanoma of the urinary bladder is a rare clinical entity, with only twenty-three published cases to date. We present a case of this rare entity, a thorough review of the literature, and differential diagnosis of melanoma in the bladder. Methods and Results. A 55-year-old woman with a history of malignant melanoma of the right thigh, excised eight years ago, presented with back pain, fatigue, and hematuria. She underwent computed tomography (CT) scan and was found to have metastases within the liver, spleen, lungs, and urinary bladder. She underwent cystoscopy and transurethral resection of three polypoid lesions. Histologic and immunohistochemical examination revealed metastatic malignant melanoma involving bladder mucosa. Conclusions. This case illustrates the importance of including malignant melanoma in the differential diagnosis of high grade neoplasms of bladder, especially in cases where the relevant clinical history is not available.